The Potential For Scaling Up Container-Based Sanitation In Informal Settlements In Kenya - mallory, adrian; Mdee, Mdee; Agol, Dorice; Hyde-Smith, Leonie; Kiogora, Domenic; Riungu, Joy; Parker, Alison (My University, 2022)
Kenya has enshrined the right to sanitation in the 2010 constitution. Achieving this requires scaling up infrastructure and models of delivery beyond sewer networks that have previously been the focus. In Kenya, two enterprises, Sanergy and Sanivation, have been providing new forms of off-grid services with container-based sanitation (CBS). This paper uses a political economy analysis to understand the incentives, institutions and power dynamics that are enabling or constraining the potential for such off-grid sanitation models. The paper outlines six core problems to be addressed in the pursuit of scaling up: fragmented governance; sustainability of CBS enterprise models; service delivery planning in informal settlements; personal power rather than institutions in decision-making; vested local interests; and land tenure and political connection. It discusses how stakeholders might work collaboratively to progressively address or recognise these issues.
Keywords: Wastewater Treatment Processes; Social Enterprises; Political economy